Ustadz Abdul Somad's Rhetorical Style of Preaching in a Sermon Commemorating the Birthday of the Prophet Muhammad SAW in 1440 H at the Baiturrahman Grand Mosque, Banda Aceh - Shulistia (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The purpose of this study is to determine the rhetorical style of Ustadz Abdul Somad's da'wah when delivering his lecture in Aceh. This study focuses on when Ustadz Abdul Somad lectured at the Baitturrahman Grand Mosque in Banda Aceh. The theory used in this study is Aristotle's rhetorical theory, namely the five canons of rhetoric which focuses on the study of Elocutio / Style (language style and body movement style), using the Gorys Keraf concept. This study uses a qualitative method that is descriptive analysis. The data collection technique used in this study is data obtained through video recording documentation and also obtained through direct informant interviews. To analyze the data, this study uses the Miles and Huberman data analysis model, while the selection of informants uses the key informant method. The results of the study show that Ustadz Abdul Somad applies rhetorical style very much when delivering his lecture. Ustadz Abdul Somad applies language style based on word choice, language style based on tone, language style based on sentence structure and language style based on the directness or indirectness of meaning. Ustadz Abdul Somad also employs a style of body language when delivering sermons, including dressing modestly, standing upright, displaying facial expressions and hand gestures, and even looking at the entire congregation. Overall, the findings revealed that Ustadz Abdul Somad did not study rhetoric and never prepared any concepts for his sermons. In each sermon, Ustadz Abdul Somad simply delivered based on his direct knowledge. Therefore, Ustadz Abdul Somad's rhetoric has been spontaneous and intuitive.